2017
DOI: 10.1101/gad.295402.116
|View full text |Cite
|
Sign up to set email alerts
|

Different requirements of functional telomeres in neural stem cells and terminally differentiated neurons

Abstract: Telomeres have been studied extensively in peripheral tissues, but their relevance in the nervous system remains poorly understood. Here, we examine the roles of telomeres at distinct stages of murine brain development by using lineage-specific genetic ablation of TRF2, an essential component of the shelterin complex that protects chromosome ends from the DNA damage response machinery. We found that functional telomeres are required for embryonic and adult neurogenesis, but their uncapping has surprisingly no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…These results suggest that proper telomere maintenance is essential to maintain the proliferative capacity of NPCs. In support of this notion, telomere end-protection is critical for NPC survival during brain development, as removal of either TRF2 or POT1a elicits DNA damage signaling and massive cell death in neuronal stem cells of developing murine brains [100][101][102] . Taken together, these observations suggest that proper telomere function is required for proliferation of neuronal progenitors and neurogenesis, and further support our hypothesis that telomere dysfunction may underlie neural development defects in MCPH1 patients bearing mutated MCPH1.…”
Section: Discussionmentioning
confidence: 89%
“…These results suggest that proper telomere maintenance is essential to maintain the proliferative capacity of NPCs. In support of this notion, telomere end-protection is critical for NPC survival during brain development, as removal of either TRF2 or POT1a elicits DNA damage signaling and massive cell death in neuronal stem cells of developing murine brains [100][101][102] . Taken together, these observations suggest that proper telomere function is required for proliferation of neuronal progenitors and neurogenesis, and further support our hypothesis that telomere dysfunction may underlie neural development defects in MCPH1 patients bearing mutated MCPH1.…”
Section: Discussionmentioning
confidence: 89%
“…The role of telomere biology in brain development has been evaluated in a conditional knockout of the shelterin protein TRF2 mouse model. 19 By knocking out TRF at different stages of neuronal differentiation, the authors showed that intact telomeres are essential for embryonic and adult neurogenesis. Specifically, TRF2 knockout resulted in uncapping of telomeres and a small dentate gyrus due to loss of granule cells in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase, a reverse transcriptase, is required for embryonic and adult neurogenesis (Lobanova et al, 2017 ). To investigate whether telomerase is implicated in the E2 mediated protection of NSCs in APP/PS1 mice, we analyzed the levels of TERT and telomerase activity in 10-month-old APP/PS1 mice.…”
Section: Resultsmentioning
confidence: 99%